Contemporary carbene chemistry - Moss, Robert A.; Doyle, Michael P. (Hoboken, New Jersey : Wiley, 2014)
"The newfound stability of carbenes has led to their development as catalysts and ligands for metal complexes of vast potential, including biomolecule labeling and surface modification of materials. Providing a fresh evaluation of the field, Contemporary Carbene Chemistry explores novel structural, catalytic, and organometallic aspects of carbene chemistry. Chapters focus on the most interesting, fruitful, and promising directions in their topical areas. Featuring a chapter by Nobel Laureate Robert Grubbs, this timely text provides graduate students with the most innovative and promising aspects of carbene research over the past decade"--
"Providing a fresh evaluation of the field, Contemporary Carbene Chemistry explores novel structural, catalytic, and organometallic aspects of carbene chemistry. Chapters focus on the most interesting, fruitful, and promising directions in their topical areas"--
Machine generated contents note: Preface PART 1: PROPERTIES AND REACTIONS OF CARBENES 1. Carbene Stability / S. Gronert and R.M. O'Ferrall -- 2. Stable Carbenes / J.P. Moerdyk and C.W. Bielawski -- 3. Acid-Base Chemistry of Carbenes / A.M. O'Donoghue and R.S. Massey -- 4. Computational Methods for the Study of Carbenes and their Excited States / H.L. Luk, S. Vyas, and C.M. Hadad -- 5. Dynamics in Carbene Reactions / D. Merrer, K. Houk, and L. Xu -- 6. Ultrafast Kinetics of Carbene Reactions / G. Burdzinski and M.S. Platz -- 7. Tunneling in the Reactions of Carbenes and Oxacarbenes / D. Gerbig and P.R. Schreiner -- 8. Carbodicarbenes / G. Frenking and R. Tonner -- 9. Catalytic Reactions with N-Mesityl Substituted N-Heterocyclic Carbenes / J. Mahatthananchai and J.W. Bode -- 10. Supramolecular Carbene Chemistry / U. Brinker, J.-L. Mieusset, and M.G. Rosenberg -- PART 2: METAL CARBENES 11. Modern Lithium Carbenoid Chemistry / V. Capriati -- 12. Rhodium Carbenes / H. Davies and B. Parr -- 13. Ruthenium Carbenes / S.T. Diver and J.M. French -- 14. Nucleophilic Carbenes of the Chromium Triad / Z.J. Tonzetich -- 15. Cobalt-Mediated Carbene Transfer Reactions / X. Cui and X.P. Zhang -- 16. Gold Carbenes / L. Zhang.
Machine generated contents note: Preface PART 1: PROPERTIES AND REACTIONS OF CARBENES 1 Carbene Stability S. Gronert and R.M. O'Ferrall 2 Stable Carbenes J.P. Moerdyk and C.W. Bielawski 3 Acid-Base Chemistry of Carbenes A.M. O'Donoghue and R.S. Massey 4 Computational Methods for the Study of Carbenes and their Excited States H.L. Luk, S. Vyas, and C.M. Hadad 5 Dynamics in Carbene Reactions D. Merrer, K. Houk, and L. Xu 6 Ultrafast Kinetics of Carbene Reactions G. Burdzinski and M.S. Platz 7 Tunneling in the Reactions of Carbenes and Oxacarbenes D. Gerbig and P.R. Schreiner 8 Carbodicarbenes G. Frenking and R. Tonner 9 Catalytic Reactions with N-Mesityl Substituted N-Heterocyclic Carbenes J. Mahatthananchai and J.W. Bode 10 Supramolecular Carbene Chemistry U. Brinker, J.-L. Mieusset, and M.G. Rosenberg PART 2: METAL CARBENES 11 Modern Lithium Carbenoid Chemistry V. Capriati 12 Rhodium Carbenes H. Davies and B. Parr 13 Ruthenium Carbenes S.T. Diver and J.M. French 14 Nucleophilic Carbenes of the Chromium Triad Z.J. Tonzetich 15 Cobalt-Mediated Carbene Transfer Reactions X. Cui and X.P. Zhang 16 Gold Carbenes L. Zhang.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Carbenes (Methylene compounds); Carbon compounds; SCIENCE -- Chemistry -- Physical & Theoretical; Carbenes (Methylene compounds); Carbon compounds; Carbene; Electronic books; Electronic books